2009
DOI: 10.1093/jaoac/92.5.1519
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Linked Immunosorbent Assay Kit for Beta-Lactoglobulin Determination: Interlaboratory Study

Abstract: An interlaboratory study was performed in six laboratories to prove the validation of the ELISA method developed for quantitative determination of beta-lactoglobulin (BLG) in foods. The ELISA kit used for this study is based on rabbit polyclonal antibody. In-house validation of the kit did not produce false-positive results or cross-reactivity in a broad range of food matrixes containing no milk proteins. All participants obtained the BLG kit with a standard operational procedure, the list of the samples, samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…An inter-laboratory study was performed in order to validate an ELISA kit based on a rabbit polyclonal antibody for the quantitative determination of BLG in foods (Stumr et al, 2009). The LOD was 0.07 mg BLG/kg and the LOQ was 0.22 mg BLG/kg.…”
Section: Elisamentioning
confidence: 99%
“…An inter-laboratory study was performed in order to validate an ELISA kit based on a rabbit polyclonal antibody for the quantitative determination of BLG in foods (Stumr et al, 2009). The LOD was 0.07 mg BLG/kg and the LOQ was 0.22 mg BLG/kg.…”
Section: Elisamentioning
confidence: 99%
“…Whereas, the high background signal was suspected to originate from the use of pAbs as BLG capturing agent. Stumr et al 41 reported the rabbit pAb-based BLG detection kit with a LOD of 0.07 mg/kg. The commercial ELISA kit against BLG has indicated the cross-reaction with hydrolytic peptides.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%